2011
DOI: 10.1007/s11631-011-0497-3
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy, M-type tetrad effect and radioactivity of altered granites at the G. Abu Garadi shear zone, central Eastern Desert, Egypt

Abstract: The G. Abu Garadi area is covered mainly by metasediments, alkali feldspar granites and stream sediments. The alkali feldspar granite is traversed by a major strike-slip fault trending in an N-S direction as well as two subordinate sets of faults trending NW to WNW for the first one and NE for the second one. These faults represent the shear zones affected by magmatic (syngenetic) as well as hydrothermal (epigenetic) activities causing alteration of the granitic rocks. The most common alteration features are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Abedini et al (2018) indicated that the co-existence of W-and Mshape tetrad-effects in the Kanigorgeh residual horizon of bauxite deposits in Iran supports the idea that penetration of low-pH surface waters into the upper part caused destruction of REE-bearing minerals, leaching and transportation of REE downwards and their ultimate concentration in the lower part. Conjugate types of this effect (M-and W-shape) have been reported from different environments, such as the Qahr-Abad fluorite deposit and other deposits worldwide (El Nahas et al, 2011;El Mezayen et al, 2019, Ibrahim et al, 2015El-Tohamy, 2019). The latter indicates that the existence of both W-and M-type tetrad effects in the same deposit can be related to weathering, leaching by groundwater and/or mixing of fluids and/or waters or combinations of these.…”
Section: Genesis Of Tetrad Effectsmentioning
confidence: 91%
“…Abedini et al (2018) indicated that the co-existence of W-and Mshape tetrad-effects in the Kanigorgeh residual horizon of bauxite deposits in Iran supports the idea that penetration of low-pH surface waters into the upper part caused destruction of REE-bearing minerals, leaching and transportation of REE downwards and their ultimate concentration in the lower part. Conjugate types of this effect (M-and W-shape) have been reported from different environments, such as the Qahr-Abad fluorite deposit and other deposits worldwide (El Nahas et al, 2011;El Mezayen et al, 2019, Ibrahim et al, 2015El-Tohamy, 2019). The latter indicates that the existence of both W-and M-type tetrad effects in the same deposit can be related to weathering, leaching by groundwater and/or mixing of fluids and/or waters or combinations of these.…”
Section: Genesis Of Tetrad Effectsmentioning
confidence: 91%
“…Secondary generated quartz and uranium mineralization show an intimate intergrowth in microfractures. In some parts, the amorphous silica coating the mineralized surface, and may protect them from alteration (El Feky, 2011).…”
Section: Geologic Outlinesmentioning
confidence: 99%
“…4). (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) were assayed to determine the variation of concentrations with pH on this protocol. The concentrations determined using this modified method was not affected significantly with the variation in the pH from 2 to 8.…”
Section: Effect Of Reagent Volumesmentioning
confidence: 99%
“…Uranium ore always contains other metal impurities 5 , so the leaching, adsorption, or biosorption of Uranium vary according to the type of the rock 6,7 . Many techniques have been previously developed for the determination of Uranium; these methods include inductively coupled plasma spectrometry (ICP-AES) 8 , inductively coupled plasma-mass spectrometry (ICP-MS) 9,10 , ion chromatography (I.C.)…”
Section: Introductionmentioning
confidence: 99%